Using GPS-based link exclusion to reduce overhead and increase route reliability in FTP/TCP-based MANETs. (17th December 2009) - Phillips, Aaron L.; Matis, Timothy I.
In this paper, we show that the use of global positioning system (GPS) information in a mobile ad hoc network (MANET) running the file transfer protocol (FTP) over the transmission control protocol (TCP) can be used to block the inclusion of unreliable links within a discovered route by not allowing the nodes outside of a given distance to participate in their formation. In doing so, this creates more reliable routes over time and lowers the amount of network overhead necessary to maintain the flow of data packets. This approach to route formation is validated using the NS-2.31 network simulator under different types of multipath fading models as well as varying network dimensions and node densities. While this GPS blocking scheme has been explored previously in a constant bit rate (CBR) over a user datagram protocol (UDP) setting, it has not yet been tested previously under the more common real-world conditions of FTP running over TCP.